Psychic Hacking: Using Remote Viewing to Steal Computer Data - Wichmann, Scotch (Journal of Scientific Exploration, 2026)
This article presents exploratory experimental results suggesting that some individuals with remote viewing abilities may be able to describe details of data present in computers located miles away. Building on past U.S. Government psi research, an Internet-hosted experiment allowed participants to try using their psychic powers to describe picture, video, ATM PIN, and passphrase targets stored on laptop computers in Los Angeles. The laptops were standalone with networking capabilities disabled, configured to deploy new targets nightly without human intervention, and covered with sleeves to prevent peeking. A total of 146 remote participants generated 584 free-response rounds. Each round was scored by three independent judges chosen randomly from a pool of six. Judging employed rank-order scoring, and counting the number of target details matched. Many participants successfully described targets to a degree sufficient to reject the null hypothesis. Statistically significant results (α = 0.05) were observed for both picture (p = 0.000597, h = 1.075) and video targets (p = 0.000911, h = 1.131). ATM PIN results were significant for 3 digits in any order (p = 4.118 × 10−6, h = 0.788) and 2 digits in any order (p = 7.84 × 10−6, h = 0.763). Security and privacy implications of “psychic hacking” may be far-reaching, since physical distance, attenuating structures, visual shielding, network air gaps, data obfuscation, strict file permissions, and file monitoring failed to detect or prevent data theft.